2019
DOI: 10.13189/ujer.2019.071234
|View full text |Cite
|
Sign up to set email alerts
|

Determinant Factors of Development Entrepreneurial Education: Lesson from Senior High School in Indonesia

Abstract: This study aims to obtain information and knowledge related to entrepreneurial education, subjective norm, and entrepreneurial attitude towards entrepreneurial intention senior high school student. This research followed a survey method with proportional random sampling technique while the data was primary data obtained by 251 respondents from three senior high school in Jakarta, Indonesia. Furthermore, the data were analyzed using AMOS Structural Equation Modeling (SEM) in order to understand the direct influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Education, from high school through college, represents a determining factor in encouraging entrepreneurial attitudes; other potential factors include family background, peer groups and economic literacy (Jena, 2020;Karyaningsih et al, 2020;Suratno et al, 2021). Some studies have shown that there is a positive effect of entrepreneurial education on entrepreneurial attitude, and this increases students' entrepreneurial intentions (Saptono et al, 2019). Universities, as the main institutions for talent training, should make entrepreneurial talents their main educational goal (Zine et al, 2019).…”
Section: Theoretical Framework 21 Entrepreneurial Attitudementioning
confidence: 99%
“…Education, from high school through college, represents a determining factor in encouraging entrepreneurial attitudes; other potential factors include family background, peer groups and economic literacy (Jena, 2020;Karyaningsih et al, 2020;Suratno et al, 2021). Some studies have shown that there is a positive effect of entrepreneurial education on entrepreneurial attitude, and this increases students' entrepreneurial intentions (Saptono et al, 2019). Universities, as the main institutions for talent training, should make entrepreneurial talents their main educational goal (Zine et al, 2019).…”
Section: Theoretical Framework 21 Entrepreneurial Attitudementioning
confidence: 99%
“…The attitudes of a graduate being able to create, problem solving, energinism, converting challenges into opportunities, eager to learn new things, risk taking, on job pressure handling are affection attributes leant following exposures (Donlan, 2018). Leadership, team working spirit is due to exposure to practical environment Saptono & Najah, 2018). This learning activity either requires collaboration i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Since the increasing concern on manifold entrepreneurs in Indonesia, entrepreneurship education needs be promoted from primary school to the university level. However, the existing studies in Indonesia mainly focus on the level of university students ( Kusmintarti et al., 2016 ; Patricia and Silangen, 2016 ), senior high school ( Purwana et al., 2018 ; Saptono et al., 2019 ), vocational schools ( Eryanto et al., 2019 ; Wardana et al., 2020 ), while the concern on elementary students has been overlooked by scholars. Additionally, some previous studies have undervalued the essentials of outdoors for children's development.…”
Section: Introductionmentioning
confidence: 99%